Information systems : what every business student needs to know - Mallach, Efrem, 1942- (Boca Raton, FL : CRC Press LLC, 2020)
Most information systems textbooks overwhelm business students with overly technical information they may not need in their careers. This textbook takes a new approach to the required information systems course for business majors. For each topic covered, the text highlights key "Take-Aways" that alert students to material they will need to remember during their careers. Sections titled "Where You Fit In" and "Why This Chapter Matters" explain how the topics being covered will impact students on the job. Review questions, discussion questions, and summaries are also included. This second edition is updated to include new technology, along with a new running case study. Key features: Single-mindedly for business students who are not technical specialists Doesnt try to prepare IS professionals; other courses will do that Stresses the enabling technologies and application areas that matter the most today Based on the authors real-world experience Up to date regarding technology and tomorrows business needs This is the book the authorand, more importantly, his studentswishes he had when he started teaching. Dr. Mallach holds degrees in engineering from Princeton and MIT, and in business from Boston University. He worked in the computer industry for two decades, as Director of Strategic Planning for a major computer firm and as co-founder/CEO of a computer marketing consulting firm. He taught information systems in the University of Massachusetts (Lowell and Dartmouth) business schools for 18 years, then at Rhode Island College following his retirement. He consults in industry and serves as Webmaster for his community, in between hiking and travel with his wife.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Management information systems; Business -- Data processing; Business -- Information technology; Information technology -- Management; BUSINESS & ECONOMICS / Information Management; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design